Handbook of research on energy-saving technologies for environmentally-friendly agricultural development - Kharchenko, Valeriy, 1938-; Vasant, Pandian (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
"This book examines the research and development of new technologies and effective technical means to solve the problem of energy consumption decrease in the agricultural industrial sector and in the housing and communal services sector in the countryside"--Provided by publisher.